Stress background and rock fractures revealed by ultrasonic borehole television in the Fankou Lead-Zinc Mine - Du, Yi; Wu, Chengfei; Wang, Chenghu; Yuan, Guiqiang; Ouyang, Shiyuan; Liao, Jie; An, Yifei (Frontiers in Earth Science, 2023)
The stress background and rock fractures are essential factors affecting the stability of mines. In order to better understand the in situ stress background and rock fractures in the Guangdong Fankou Mine, we use ultrasonic borehole television scanning to measure rock fractures. The results indicate that rock fractures are intensively distributed at depths of -360 m to -450 m below the surface, suggesting the effect of intensive mining activities. The present maximum horizontal principal stress direction is NWW, which is consistent with the regional tectonic stress field direction. Systematic measurement of rock fractures is fundamental for further three-dimensional geological modeling and is significant for mining engineering.